Population policy of India : implementation strategies at national and state levels - Population policy of India; Saxena, B. N.; Wadhva, Charan D.; Sharma, O. P. (New Delhi : Sterling Publishers, 2004)
Papers presented at the conference organized by Centre for Policy Research.
"Centre for Policy Research, New Delhi."
Keywords: Population Policy; India